Enabling 5G Communication Systems to Support Vertical Industries 2019
DOI: 10.1002/9781119515579.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Vehicular Communications within the Context of 5G Systems

Abstract: Future autonomous transportation systems necessitate network infrastructure capable of accommodating massive vehicular connectivity, despite the scarce availability of frequency resources. Current approaches for achieving such required high spectral efficiency, rely on the utilization of Multiple-Input, Multiple-Output (MIMO) technology. However, conventional MIMO processing approaches, based on linear processing principles, leave much of the system's capacity heavily unexploited. They typically require a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The previous studies and field measurements have been performed to analyze the performance and suitability of IEEE 802.11p and LTE in different V2X scenarios 14 . This performance analysis concluded that both technologies are suitable for allowing basic vehicular communication that is, transferring Cooperative Awareness Message (CAM).…”
Section: Advanced Standardization Of Vehicular Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies and field measurements have been performed to analyze the performance and suitability of IEEE 802.11p and LTE in different V2X scenarios 14 . This performance analysis concluded that both technologies are suitable for allowing basic vehicular communication that is, transferring Cooperative Awareness Message (CAM).…”
Section: Advanced Standardization Of Vehicular Communicationmentioning
confidence: 99%
“…However, the advantage of IEEE 802.11p in contrast of LTE is that it has been implemented, analyzed, verified to use this technology for vehicular communication. Though, the benefit of using cellular based LTE is that the similar software and hardware protocols have been utilized 14 . The new technology, for example, 5G, is expected to have an improved performance in terms of latency and reliability as compared to other predecessor technologies.…”
Section: Advanced Standardization Of Vehicular Communicationmentioning
confidence: 99%
“…The most promising RAT is the 5G New Radio (NR), which proposes a dedicated service oriented core for CAVs. Furthermore, 5G affiliated technologies such as Cloud Radio Access Network (CRAN) employing Mobile Edge Computing (MEC) are becoming favourites for achieving robust and low latency communications [5].…”
Section: F I G U R E 1 5g Communication Network For Cavsmentioning
confidence: 99%
“…We observed that underlying communication technology was necessary to ensure efficient operation of the overall system. Even though many communication technologies exist and newer technologies like 5G are gaining momentum [26], [27], the RACE framework is agnostic to these technologies. Therefore, we made one assumption that any underlying communication technology that fulfills the requirements for performance, latency and parameter distribution in an autonomous driving environment could be used in RACE.…”
Section: A Assumptionsmentioning
confidence: 99%